Disentangling the role of the exchange rate in oil-related scenarios for the European stock market - Javier Ojea Ferreiro (European Central Bank (ECB), 2019)
Until now, stock market responses to a distress scenario for oil prices have been analysed considering prices in domestic currency. This assumption implies merging the commodity risk with the exchange rate risk when oil and stocks are traded in different currencies. This article proposes incorporating explicitly the exchange rate, using the convolution concept, to assess how could change the stock market response depending on the source of risk that moves oil prices. I apply this framework to study the change in the 10th lowest percentile of the European stock market under an oil-related stress scenario, without overlooking the role of the exchange rate. The empirical exercise shows that the same stress oil-related scenario in euros could generate an opposite impact in the European stock market depending on the source of risk. The source of risk is not incorporated when performing a bivariate analysis, which suggests ambiguous estimates of the stock response. This framework can improve our understanding of how the exchange rate interacts in global markets. Also, it contributes to reduce the inaccuracy in the impact assessment of foreign shocks where the exchange rate plays a relevant role.
Keywords: E30; E37; E44; G10; 330; Convolution; stress test; Exchange rate; spillover analysis